Produção de bioprodutos a partir do cultivo batelada e batelada alimentada de Phormidium autumnale em vinhaça de cana-de-açúcar - Visentin, Taisne Gonçalves (Universidade Federal de São Carlos, 2020)
Processes using microalgae and cyanobacteria in the treatment of wastewaters have been attractive due to the obtaining of biomass with the commercial value associated and the efficient removal of some contaminants. The cultivation of these microorganisms with biomass generation and obtaining bioproducts such as proteins, lipids, carbohydrates and pigments is known by the term "microalgal biorefinery." In this context, this research aimed the heterotrophic cultivation of filamentous cyanobacteria Phormidium autumnale in sugarcane vinasse, evaluating the removal of contaminants with an emphasis on obtaining value added bioproducts. In the first stage, the highest productivity in biomass was obtained from a central composite rotational design (CCRD) in an orbital shaker, being 127.20 mg/L/h and 107.91 mg/L/h at 31ºC and 35ºC, respectively, in initial C/N ratios of 16 and 23 and initial pH of 8.4 and 7.5. In these conditions at 35ºC, removals of organic carbon, nitrogen, and phosphorus were 49%, 47%, and 28%, respectively. In the cultivation in a batch bioreactor were obtained the removals of organic carbon (67%) and nitrogen (70%), with maximum productivity in terms of biomass equivalent to the best condition of the tests carried out in an orbital shaker (CCRD). The biomass of P. autumnale generated in a batch bioreactor showed 21.33% of proteins, 4.26% of lipids, with important fatty acids for the production of biodiesel, 197.53 mg phycocyanin/g biomass of phycocyanin, varied composition of carbohydrates (glucose 79.46 mg/L, arabinose 44.53 mg/L, mannose 9.84 mg/L, galactose 4.78 mg/L, and xylose 14.44 mg/L) and 0.97 g/L of total reducing sugars. Cultivation in a fed-batch bioreactor generated 43.51% of proteins, 12.6% of lipids with fatty acid composition for biodiesel synthesis, carbohydrates such as glucose (48.06 mg/L), arabinose (53.33 mg/L), mannose (26.95 mg/L) and galactose (2.76 mg/L), as well as 0.81 g/L of total reducing sugars and 99.5 mg phycocyanin/g biomass of phycocyanin. The results indicated the technical feasibility of growing this cyanobacterium in sugarcane vinasse in batch and fed-batch cultivations, with carbon and nitrogen removals. Also, its composition in terms of proteins, carbohydrates, and lipids indicates possible applications for the biomass generated, indicating the possibility of this microalgae being integrated into a biorefinery system with the sugar-energy industry.
Bioproducts production in batch and fed-batch cultivation of Phormidium autumnale from sugarcane vinasse
Keywords: Cianobactéria; Cultivo heterotrófico; Biorrefinaria; Efluente; Microalgas; Cyanobacteria; Heterotrophic cultivation; Biorefinery; Wastewater; Microalgae; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS